Comorbidity of Celiac Disease and Autoimmune Hemolytic Anemia in a Patient - Ahmad, Neelam (International Journal of Pathology, 2023)
Background: Celiac Disease (CD) is an autoimmune condition caused by consumption of food containing gluten. The condition gets worse while occurring simultaneously with another autoimmune disease known as Auto Immune Hemolytic Anemia (AIHA). In the study, a case is reported who had two conditions simultaneously.Objectives: The objective is to report a rare case that has both CD and AIHA.Material and MethodsUpon reception, a patient undergone testing and screenings to have first hand data. After series of screenings, when some of the serological tests showed connection with celiac diseases, Coombs test and biopsy was performed to rule out the possibility of autoimmune hemolytic anemia. Results: The results were obtained from the serological and screenings and they confirmed the existence of co-morbidity of CD with AIHA. Retic count showed raise by 15%. Bone marrow showed all cell lines intact but increased erythroid hyperplasia. Iron showed an increase in bone marrow with siderocytes and sideroblasts.Conclusion: It was concluded from the study that CD and AIHA can co-exist and cause more complications